1999
DOI: 10.1007/s007840050088
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol-A content of resin monomers and related degradation products

Abstract: Recently, it was reported that Bisphenol-A (BPA) was released from one fissure sealant (Delton) into saliva causing estrogenic activity in vitro. The aim of this study was to chemically analyze the BPA content of different fissure sealant resin monomers and their release of BPA under hydrolytic conditions. BPA content was first measured in commercially available monomers of bisphenol-A glycidyldimethacrylate (Bis-GMA), bisphenol-A dimethacrylate (Bis-DMA) and bisphenol-A diglycidylether (BADGE). Then, Bis-GMA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
100
2
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 15 publications
3
100
2
5
Order By: Relevance
“…BPA was found in the saliva within few minutes after a dental treatment, but at considerably lower levels than previously reported. BPA became undetectable 1 and 24 h after the placement of the sealant [10,12]. It was concluded that due to the low level of BPA, there was no clinical risk after placement of fissure sealants, an assumption that was confirmed by other authors [10,13,14].…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…BPA was found in the saliva within few minutes after a dental treatment, but at considerably lower levels than previously reported. BPA became undetectable 1 and 24 h after the placement of the sealant [10,12]. It was concluded that due to the low level of BPA, there was no clinical risk after placement of fissure sealants, an assumption that was confirmed by other authors [10,13,14].…”
mentioning
confidence: 59%
“…BPA became undetectable 1 and 24 h after the placement of the sealant [10,12]. It was concluded that due to the low level of BPA, there was no clinical risk after placement of fissure sealants, an assumption that was confirmed by other authors [10,13,14]. Indeed, considering the dose-response, the BPA level was too low to be toxic if the disease is linked to the amount of BPA released during dental treatment.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The concentration of released Bis-GMA from certain types of sealants has been reported to be within the range at which estrogen receptor-mediated effects were seen in rodents (Schmalz et al 1999). However, the release from resin based restoratives is much lower.…”
Section: Generalmentioning
confidence: 98%
“…Therefore, leaching of a small amount of unpolymerized BPDMA is likely (3,4). Furthermore, the detection of BPA derived from BPDMA in saliva is likely because BPDMA is easily hydrolyzed to BPA in saliva (6) Olea's Response…”
mentioning
confidence: 99%